Here, Hidden, in My Head (3H) Strategy: an Interactive Solution to Increase Students’ Reading Comprehension - Mike Amelia; Yosi Delfitra (Jurnal Educative: Journal of Educational Studies, 2020)
The eighth-grade students of SMPN 2 Danau Kembar of West Sumatra, Indonesia, had a problem with their reading skills since they unexpectedly did not understand the texts well. The implementation of an inappropriate learning strategy was criticized as one of the factors contributing to the problem. This study aimed to determine the impact of the 3H strategy on increasing the student's ability to understand the descriptive text. It was quasi-experimental research in which two classes were assigned to experimental and control classes. Each class consisted of 24 pupils (VIII-A) as an experimental class, and 24 pupils (VIII B) as a control class were selected as a sample through an objective inspection. The mean score of understudy reading perception in the test class is 75.71 higher than the mean score of student reading comprehension in the control class is 69.54. The researcher was given 2,91 for the data T calculated and 1,68 for the Ttable. Overall, H0 was rejected, and Ha was received. In view of the findings of the research, teaching reading through the use of the 3H strategy has a positive effect on students reading understanding.Permasalahan yang dihadapi oleh siswa kelas delapan SMPN 2 Danau Kembar di Sumatera Barat, Indonesia dalam kemampuan mereka dalam memahami teks merupakan landasan dasar permasalahan dari penelitian ini. Diantaranya ditemukan fakta bahwa kemampuan siswa memahami teks berada dibawah standar yang diharapkan. Ha ini dikarenakan beberapa faktor salah satunya adalah lemahnya strategi yang digunakan pada saat proses pembelajaran. Tujuan penelitian ini adalah untuk megetahui efek dari strategi 3H (Here, Hidden, and in my Head) dalam memahami teks deskriptif. Metode riset ini adalah quasy experiment. Siswa kelas delapan SMP N 2 Danau Kembar merupakan populasi penelitian ini.  Kelas VIIIA (24 orang) sebagai kelas experimen dan kelas VIII B (24 orang) sebagai kelas kontrol merupakan kelas sampel yang dipilih dengan menggunakan teknik purposive sampling.  Pada kelas experimen diperoleh rerata 75,71, sementara itu rerata kelas kontrol adalah 69,54. Peneliti juga mendapatkan Tcalculated sebesar 2,91 dan Ttable sebesar 1,68. Dari data yang didapatkan jelaslah bahwa H0 ditolak dan Ha diterima. Dengan demikian dapat disimpulkan bahwa penggunaan strategi 3H memberikan efek positif dan dapat meningkatkan kemampuan pemahaman membaca siswa pada teks deskrptif.